Transgenic expression of the human LEDGF/p75 gene relieves the species barrier against HIV-1 infection in mouse cells - Tada, Takuya; Kadoki, Motohiko; Yang, Liu; Tokunaga, Kenzo; Iwakura, Yoichiro (Frontiers in Microbiology, 2013)
Attempts to create mouse models for AIDS have been hampered by species barriers in HIV-1 infection. We previously showed that the nuclear accumulation of HIV-1 preintegration complex (PIC) was suppressed in mouse cells. Lens epithelium-derived growth factor (LEDGF/p75) is a host factor identified as a binding partner of integrase (IN), and has been suggested to be involved in promoting viral integration by tethering PIC to the chromatin, which are observed as nuclear accumulation of IN by LEDGF/p75. Therefore, we here hypothesized that this host factor might act as one of the species-specific barriers in mouse cells. We generated transgenic (Tg) mice that constitutively express human (h) LEDGF/p75. The GFP-fused IN was efficiently accumulated into the nucleus of hLEDGF/p75-expressing Tg mouse embryonic fibroblast (MEF) cells in contrast to the control MEF cells. Importantly, hLEDGF/p75 Tg MEF cells were significantly more susceptible to HIV-1 infection. These results suggest that LEDGF/p75 is one of host factors that constitute species barrier against HIV-1 in mouse cells.